Utilization of Preventive Health Check-Ups Among Older People in Rural Indonesia - Aji, Budi; Anandari, Dian; Masfiah, Siti; Wijayanti, Siwi Pramatama Mars; Chamchan, Chalermpol (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The use of preventive health check-ups among older people was driven by health status and socioeconomic factors. This present study identified the determinants of preventive health check-up utilization among older people in rural Indonesia. This study had been conducted in rural areas in the district of Banyumas, Central Java, Indonesia. A cross-sectional survey had been carried out and a total of 412 older people were selected by using multistage sampling. Logistic regression determined the predictors of preventive health check-up utilization. The majority of the older people were female (75.5%) with low levels of educational attainments (56.3%). Factors including chronic illnesses and uneducated were associated with preventive health check-ups among older people. Older people with chronic illnesses (p less than 0.05, OR = 6.276) were more likely to use preventive health check-ups. Further, uneducated older people (p less than 0.05, OR = 12.562) were less likely to use preventive health check-ups in rural areas. Health status becomes a prominent factor that influences health care utilization among older people. Health interventions targeting identified at-risk subgroups are potential for fulfilling the demand for health care among older people who live in the community, particularly in rural areas. Health promotion for enhancing health literacy among older people would improve the utilization of preventive health check-ups among older adults. Abstrak: Pemanfaatan layanan pemeriksaan kesehatan untuk lansia ditentukan oleh kondisi kesehatan dan faktor sosialekonominya. Kajian ini bertujuan untuk mengidentifikasi faktor-faktor determinan pemanfaatan pemeriksaan kesehatan pada lansia di wilayah pedesaan. Kajian ini dilaksanakan di Kabupaten Banyumas, Jawa Tengah, Indonesia. Survei dilakukan dengan menggunakan pendekatan belah lintang dan multistage random sampling terhadap 412 lansia. Data selanjutnya dianalisis dengan menggunakan regresi logistik. Hasil penelitian menunjukkan bahwa sebagian besar (75,5%) lansia adalah perempuan dengan tingkat pendidikan yang rendah (56,3). Status penyakit kronis dan tidak berpendidikan pada lansia berpengaruh signifikan secara statistik dengan pemanfaatan pemeriksaan kesehatan. Lansia yang memiliki penyakit kronis (p kurang dari 0,05, OR = 6,276) cenderung lebih memanfaatkan layanan pemeriksaan kesehatan, sedangkan lansia yang tidak berpendidikan (p kurang dari 0,05, OR = 12,562) cenderung kurang memanfaatkan layanan pemeriksaan kesehatan tersebut. KOndisi status kesehatan menjadi faktor utama yang mempengaruhi lansia untuk memanfaatkan layanan pemeriksaan kesehatan. Oleh karena itu intervensi kesehatan yang sesuai untuk kelompok usia berisiko tersebut pontensial untuk dapat memenuhi harapan bagi lansia yang tinggal di daerah pedesaan. Promosi kesehatan untuk meningkatan tingkat literasi terhadap pentingnya layanan kesehatan bagi lansia akan dapat meningkatkan pemanfaatan layanan kesehatan tersebut.